Primary Central Nervous System Lymphoma Mimicking the Presentation of Pituitary Apoplexy: A Case Report - Meira Goncalves, J (2023)
Pituitary lymphoma is one of the rare variants of primary central nervous system lymphoma (PCNSL), mostly arising due to the metastatic spread of systemic lymphoma. We report the case of a 69-year-old woman who initially presented to her family physician with a headache but without any other symptoms. The MRI scan revealed a sellar mass consistent with a pituitary macroadenoma. When the patient was referred to our hospital, two weeks later, the symptoms had progressed, comprising complete right-sided ophthalmoplegia and ptosis, with left-sided amaurosis. A repeat MRI revealed an increased size of the sellar mass, consistent with pituitary apoplexy. A right pterional craniotomy with partial resection of the mass was performed and an intraoperative frozen section biopsy was carried out. The final pathology revealed diffuse large B-cell lymphoma. A systemic follow-up including a whole-body CT, bone marrow aspiration, and cerebrospinal fluid studies ruled out any systemic manifestation, and the patient was HIV-negative. The patient underwent treatment with methotrexate, cytarabine, thiotepa, and rituximab for PCNSL. Although rare, PCNSL can mimic pituitary apoplexy, which needs to be considered if conservative therapy or surgery is to be offered to a patient with a radiological and clinical diagnosis of pituitary apoplexy.